Pathophysiological profile of awake and anesthetized pigs following systemic exposure to the highly lethal ricin toxin. (2nd January 2022) - Falach, Reut; Goldvaser, Michael; Halpern, Pinchas; Rosner, Amir; Sapoznikov, Anita; Gal, Yoav; Goren, Orr; Sabo, Tamar; Kronman, Chanoch; Katalan, Shahaf
Abstract: Ricin, a plant-derived toxin originating from the seeds of Ricinus communis (castor bean plant), is one of the most lethal toxins known. To date, no in-depth study of systemic exposure to ricin in a standardized large animal model has been reported. This study details for the first time the pathophysiological hemodynamic profile following systemic/intramuscular exposure to the ricin toxin in a porcine model by comprehensive cardiorespiratory monitoring of awake and anesthetized pigs. Unlike respiratory exposure to ricin, which is characterized by the development of acute respiratory distress syndrome, following intramuscular exposure to ricin respiratory parameters were grossly unaffected, however the hemodynamics of both awake and anesthetize pigs were unsustainably compromised. We show that in the early phase until approximately 24 h post-exposure, cardiac output is not impaired although one of its components, stroke volume, is relatively low. This is due to compensatory increase in heart rate, which eventually becomes insufficient. Later, distributive shock develops, characterized by severe vasodilatation (decreased systemic vascular resistance), low central venous oxygen saturation and elevation of venous-to-arterial carbon dioxide difference indicating increase in tissue oxygen demand not met by cardiac supply. These findings serve as a basis for further studies to evaluate the ability of supportive treatments such as vasoactive and inotropic drugs, to postpone the hemodynamic deterioration and thus expand the therapeutic window for the anti-ricin treatment. Such studies are of crucial importance for judicious treatment of victims of acts of bioterrorism or of intentional self-poisoning.